Recollections of the war with Mexico - Henshaw, John C., b. 1815.; Kurutz, Gary F.; ebrary, Inc. (Columbia : University of Missouri Press, 2008)
"Major John Henshaw's firsthand account of the American invasion of Mexico includes not only narratives of the war's major battles but also forceful critiques of military leadership and strategies and vivid descriptions of Mexico's countryside, cities, and people. Editor Gary Kurutz provides extensive annotations of Henshaw's journals and letters"--Provided by publisher.
The march from Corpus Christi to the Río Grande, March-April 1846 -- The siege of Fort Texas, May-June 1846 -- An examination of the battles of Palo Alto and Resaca de la Palma -- "A fandango in Monterrey," September 1846 -- A brief history of the towns through which the American Army passed from Matamoros to Monterrey -- The march to Tampico and the Gulf of Mexico, October 9, 1846-January 22, 1847 -- The siege of Veracruz, February 20-March 20, 1847 -- Cerro Gordo and the march to Mexico City, April 4-August 10, 1847 -- Mexico City and occupation, August 11, 1847-November 6, 1847 -- Final observations on Mexico.
Includes bibliographical references (p. 233-240) and index.
Electronic reproduction.
Keywords: Henshaw, John C., -- b. 1815 -- Diaries; Henshaw, John C., -- b. 1815 -- Correspondence; Mexican War, 1846-1848 -- Personal narratives; Mexican War, 1846-1848 -- Campaigns; Electronic books